Representation of Religion and Culture of the Miduana Indigenous Community in Cianjur Regency through YouTube - Suhara, Toteng; Muhammad, Yasfi Fauzi Nur (Universitas Negeri Makassar, 2025)
The Miduana indigenous community in Cianjur Regency possesses unique cultural traditions. The interplay between culture and religion within the community is increasingly complex and mutually influential. The emergence of YouTube as a media platform has become a strategic choice to preserve these cultural uniquenesses while simultaneously fostering popular culture. YouTube serves to convey that differences in customs do not conflict with religious values but can coexist harmoniously. As a social media platform, YouTube acts as a bridge to address contemporary challenges through creative narrative content. However, media representation also carries potential risks, such as misunderstandings or stereotypical interpretations. The use of YouTube by the indigenous community can strengthen the relevance of customary practices within the religious context in the digital era. Media representation of religion and culture thus becomes a starting point for enhancing and sustaining the unique traditions of this indigenous society.